Double Dieulafoy’s lesions of the stomach in a patient with chronic renal failure on long-term hemodialysis - Eun-Ho PARK; Yeon Soon JUNG; Won Moon; Seun Ja PARK; Hark RİM (Turkish Journal of Gastroenterology, 2019)
-